ES-SCLC Patients with PD-L1+ CTCs and High Percentages of CD8+PD-1+T Cells in Circulation Benefit from Front-Line Immunotherapy Treatment - Anastasia Xagara; Argyro Roumeliotou; Alexandros Kokkalis; Konstantinos Tsapakidis; Dimitris Papakonstantinou; Vassilis Papadopoulos; Ioannis Samaras; Evagelia Chantzara; Galatea Kallergi; Athanasios Kotsakis (Biomedicines, 2024)
SCLC is an aggressive cancer type with high metastatic potential and bad prognosis. CTCs are a valuable source of tumor cells in blood circulation and are among the major contributors to metastasis. In this study we evaluated the number of CTCs that express PD-L1 in treatment-naïve ES-SCLC patients receiving ICI in a front-line setting. Moreover, we explored the percentages of different immune T-cell subsets in circulation to assess their potential role in predicting responses. A total of 43 patients were enrolled—6 of them with LS-SCLC, and 37 with ES-SCLC disease. In addition, PBMCs from 10 healthy donors were used as a control group. Different T-cell subtypes were examined through multicolor FACS analysis and patients’ CTCs were detected using immunofluorescence staining. SCLC patients had higher percentages of PD-1-expressing CD3+CD4+ and CD3+CD8+ T-cells, as well as elevated PD-1 protein expression compared to healthy individuals. Additionally, in ES-SCLC patients, a positive correlation between CD3+CD8+PD-1+ T-cells and PD-L1+ CTCs was detected. Importantly, patients harboring higher numbers of CD3+CD8+PD-1+ T-cells together with PD-L1+CTCs had a survival advantage when receiving front-line immunotherapy. Thus, this study proposes, for first time possible, immune cell–CTCs interaction, as well as a potential novel clinical biomarker for ICI responses in ES-SCLC patients.